Pengaruh Ethnocentrism Consumer dan Status Sosial Terhadap Keputusan Pembelian Ulang Produk Kosmetik Lokal di Kota Padang - Mayang Larasati; Berri Brilliant Albar; Fajri Hidayat (Fakultas Ekonomi Universitas Andalas, 2021)
This study aims to analyze the influence of consumer ethnocentrism and social status on the repurchase decision of local cosmetic products in Padang City. Type of research is causal associative research to measure the relationships between research variables or is useful for analyzing how a variable influences other variables. Respondents in this study were the people of Padang City who had purchased local cosmetic products. The number of samples is taken as many as 267 people to be used as respondents. The analysis technique used in this study is the analysis of structural equation model (SEM). The results of the study prove that: 1) Ethnocentrism has a positive and significant effect on social status in local cosmetic products in the city of Padang; 2) Ethnocentrism has no significant effect on repurchase decision of local cosmetic products in Padang City; 3) Social status has a significant effect on repurchase decision of local cosmetic products in Padang City.